Integrating Guidance and Counseling into Islamic Education: A Framework for Holistic Student Development - Fitra Herlinda; Munir Munir; Sariah Sariah (Jurnal Bimbingan dan Konseling Terapan)
This study explores the integration of guidance and counseling (GC) within Islamic education as a strategy for achieving holistic student development in an increasingly globalized world. As traditional knowledge-transfer models are insufficient to address contemporary challenges, there is a growing emphasis on character education grounded in Islamic principles such as Tawhid (oneness of Allah), Akhlak Mulia (noble character), and a spiritual-individual approach. This research employs a library-based qualitative methodology to analyze theoretical frameworks and practical strategies for embedding Islamic values into GC practices. The findings highlight the transformative potential of GC in fostering a balance between academic achievement, ethical character, and spiritual growth. By addressing personal, social, and academic challenges, GC contributes to nurturing morally upright and spiritually grounded individuals. However, challenges such as counselor competency gaps, secular-oriented curricula, and limited inter-stakeholder collaboration necessitate targeted reforms, including enhanced training, Islamically aligned curricula, and collaborative frameworks. This study positions Islamic education as a model for cultivating insan kamil—holistic individuals capable of thriving in a complex, interconnected world while upholding strong moral and ethical values. The findings offer actionable insights for educators and policymakers to design effective character education programs that integrate cognitive and moral dimensions, ensuring students are equipped to contribute meaningfully to society.